Logistics management and e-commerce performance: A PLS-SEM analysis of Jumia operations, Abuja-Nigeria - Ibrahim, Ahmed Abdullahi; Jiddah, Salihu Adam; Buhari, Muhammed (International Journal of Management and Sustainability, 2025)
E-commerce performance is increasingly crucial in Nigeria’s rapidly expanding digital marketplace, yet logistics challenges persist, threatening the sustainability and competitiveness of leading firms like Jumia. Despite market growth, a gap exists in understanding how specific logistics management practices, particularly order processing and information flow, impact e-commerce performance in Abuja. This study aims to assess the effects of order processing and information flow on Jumia’s operational outcomes in Abuja, FCT. Employing a survey research design, data were collected from all 187 Jumia employees in Abuja using structured questionnaires. A partial least squares structural equation modeling (PLS-SEM) was used. Among the key findings, it is notable that the efficient processing of orders has a strong positive influence on Jumia’s performance, increasing customer satisfaction and repeat purchases. Conversely, information flow within this study had a highly negative effect on performance, attributed to information overload and inefficiencies. It is not about the quantity or speed of information flow but its quality and management, contrasting traditional expectations. This observation indicates that Jumia’s logistics operations urgently need enhancement in information filtering and processing to maximize performance. Based on these insights, the study proposes that Jumia Nigeria should adopt new order management systems, streamline warehouse activities, and provide specialized staff training. Additionally, it is important to establish effective information filtering systems and communication channels to report incidents. These steps are likely to improve operational effectiveness, customer satisfaction, and the company’s competitive position in Nigeria’s e-commerce industry.